Preparation method and application of surface hydroxylation monatomic catalyst with Co-O-Zn structure

By preparing a surface hydroxylated single-atom catalyst with Co-O-Zn structure, the problems of low stability in the acidic environment and difficulty in selective regulation of multiple oxidants are solved, and high-efficiency degradation of sulfamethoxazole and good anti-interference ability are achieved.

CN119701971AActive Publication Date: 2025-03-28CHONGQING UNIV

Patent Information

Application Number
CN202510041388.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-28
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Existing single-atom catalysts have low stability in acidic environments, making it difficult to effectively activate multiple oxidants and selectively generate active species, limiting their applicability in different oxidant systems.

Method used

Zinc acetate and cobalt acetate are used as metal sources and dimethylimidazole as ligands, and reactions are mixed in methanol, washed, dried and calcined by centrifugation to prepare a surface hydroxylated single-atom catalyst with Co-O-Zn structure.

Benefits of technology

The catalyst has an asymmetric Co-O-Zn configuration and a large number of hydroxyl groups, which can efficiently activate persulfate and peracetic acid, selectively generate active species, degrade sulfamethoxazole, and have good anti-interference ability and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701971A_ABST
    Figure CN119701971A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of antibiotic degradation, and particularly relates to a preparation method and application of a surface hydroxylation monatomic catalyst with a Co-O-Zn structure. Zinc acetate and cobalt acetate are used as metal sources, dimethylimidazole is used as a ligand, mixing reaction is carried out in a solvent, centrifugal washing, drying and calcining are carried out, the surface hydroxylation monatomic catalyst with a Co-O-Zn structure is prepared, the surface hydroxylation monatomic catalyst has an asymmetric Co-O-Zn configuration, a large number of hydroxyl groups exist on the surface, and the surface hydroxylation monatomic catalyst has the advantages that the surface hydroxylation monatomic catalyst has a good application prospect. The asymmetric coordination structure of Co-O-Zn can optimize the adsorption behavior of an oxidizing agent, effectively adjust the interaction of metal sites and the electronic structure in the catalysis process, significantly enhance the catalytic reaction, and have strong ability to resist the interference of external inorganic ions and organic matters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibiotic degradation, and more specifically relates to a preparation method and application of a surface hydroxylated single-atom catalyst with a Co-O-Zn structure. Background Art

[0002] Single-atom catalysts (SACs) have attracted widespread attention in the field of water treatment due to their efficient metal atom utilization, high catalytic activity and adjustable electronic structure. However, in real wastewater environments (especially acidic environments), the unsaturated coordination environment of the active metal center makes its stability lower than that of other heterogeneous catalysts. This instability usually leads to the leaching and diffusion of the metal center into the water, which on the one hand reduces the catalytic performance and on the other hand brings the risk of secondary pollution. In addition, in the current research on SACs, in order to achieve selective regulation of active species in oxidant systems, complex and demanding synthetic techniques are often required, and there are few reports on the activation of multiple oxidants by a SAC and the directionally regulation of active species. This limits the applicability of SACs in different oxidant systems. Therefore, designing a multifunctional SAC that can effectively activate multiple oxidants and selectively generate active species has become a difficult problem that technicians in this field need to overcome. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation method of a surface hydroxylated single-atom catalyst having a Co-O-Zn structure and its application, so as to solve the problems existing in the above-mentioned prior art.

[0004] To achieve the above object, the present invention provides the following solutions:

[0005] One of the technical solutions of the present invention is to provide a method for preparing a surface hydroxylated single-atom catalyst having a Co-O-Zn structure, the steps comprising:

[0006] Zinc acetate and cobalt acetate are used as metal sources, dimethyl imidazole is used as a ligand, mixed and reacted in a solvent, and the surface hydroxylated single atom catalyst with a Co-O-Zn structure is obtained through centrifugal washing, drying and calcination.

[0007] Furthermore, the mass ratio of zinc acetate to cobalt acetate is 1-2:0.05-0.1.

[0008] Furthermore, the mass ratio of zinc acetate to dimethylimidazole is 1-2:4-5.

[0009] Furthermore, the mixing reaction in a solvent is a mixing reaction in methanol, and the reaction time is 20-24 hours.

[0010] Furthermore, the solvent used in the centrifugal washing is methanol.

[0011] Furthermore, the drying temperature is 60-80° C. and the drying time is 10-12 hours.

[0012] Optionally, the drying method is vacuum drying.

[0013] Furthermore, the calcination temperature is 400-500°C, the heating rate is 2-5°C / min, and the holding time is 1-2h.

[0014] Furthermore, the preparation steps of the surface hydroxylated single-atom catalyst having a Co-O-Zn structure include:

[0015] S1. Dissolve 1-2 g of anhydrous zinc acetate and 0.05-0.1 g of cobalt acetate tetrahydrate in 40-50 mL of methanol and continue stirring for 5-10 min to obtain solution A.

[0016] S2, dissolve 4-5 g of dimethylimidazole in 40-50 mL of methanol, and continue stirring for 5-10 min to obtain solution B;

[0017] S3, pouring the solution B into the solution A, stirring the reaction for 20-24 hours to obtain a viscous precursor solution;

[0018] S4, the viscous precursor solution is centrifugally washed 3 times with methanol, and vacuum dried at 60-80° C. for 10-12 h to obtain a precursor material;

[0019] S5. Heating the precursor material to 400-500° C. at a heating rate of 2-5° C. / min and keeping the temperature for 1-2 hours to obtain the surface hydroxylated single-atom catalyst having a Co-O-Zn structure.

[0020] The surface hydroxylated single-atom catalyst with a Co-O-Zn structure prepared by the present invention has an asymmetric Co-O-Zn configuration and a large number of hydroxyl groups on the surface. The asymmetric coordination structure of Co-O-Zn can effectively regulate the interaction and electronic structure of metal sites in the catalytic process, significantly enhancing the catalytic reaction. The hydroxyl groups on the surface of the catalyst can effectively regulate the adsorption configuration of persulfate and peracetic acid, so that specific active species can be selectively generated. The formation of hydroxyl groups on the surface of the catalyst is due to surface oxidation, adsorption of moisture or interaction with water or oxygen during the reaction. The ZnO component in the catalyst can also self-stabilize the pH of the reaction system, maintain it in a neutral microenvironment, and increase the stability of the reaction system. It effectively solves the problem of selective regulation encountered in the activation of multiple oxidants by single-atom catalysts, and provides valuable insights for the construction of SACs with multifunctional applications.

[0021] The second technical solution of the present invention is to provide a surface hydroxylated single-atom catalyst having a Co-O-Zn structure, wherein the surface hydroxylated single-atom catalyst having a Co-O-Zn structure is prepared by the above-mentioned preparation method.

[0022] The third technical solution of the present invention is to provide an application of the above-mentioned surface hydroxylated single-atom catalyst with Co-O-Zn structure in the degradation of sulfamethoxazole.

[0023] The fourth technical solution of the present invention is to provide a method for degrading sulfamethoxazole, comprising the following steps:

[0024] The surface hydroxylated single-atom catalyst having a Co-O-Zn structure is added to a solution of sulfamethoxazole, stirred, and after reaching an adsorption-desorption equilibrium state, an oxidant is added to perform a degradation reaction of sulfamethoxazole;

[0025] The oxidizing agent includes persulfate or peracetic acid.

[0026] The surface hydroxylated single-atom catalyst with a Co-O-Zn structure prepared by the present invention is used to activate persulfate or peracetic acid to form a Fenton-like system to degrade sulfamethoxazole.

[0027] The present invention discloses the following technical effects:

[0028] In the present invention, zinc acetate and cobalt acetate are used as metal precursors to synthesize a surface hydroxylated single-atom catalyst (CoSAs-ZnO) with a Co-O-Zn structure. The Co-O-Zn configuration and the surface hydroxylated structural design can efficiently activate persulfate and peracetic acid to directionally generate active species to degrade sulfamethoxazole.

[0029] The surface hydroxylated single atom catalyst (CoSAs-ZnO) with a Co-O-Zn structure prepared by the present invention has the function of self-regulating the pH of the reaction system, and this function is exerted because ZnO is an amphoteric metal oxide that can react with both hydrogen ions and hydroxide ions. This function can maintain the neutral microenvironment of the reaction system, and no matter how the initial pH of the system changes within the range of 3 to 8, the pH of the system can be maintained at about 6 after the reaction is completed. This characteristic is conducive to maintaining the stability of the catalytic system.

[0030] The surface hydroxylated single-atom catalyst (CoSAs-ZnO) with a Co-O-Zn structure prepared by the present invention can efficiently activate peroxymonosulfate and peracetic acid in a short time, and can respectively generate sulfate radicals and singlet oxygen with high selectivity, efficiently degrade sulfamethoxazole, and has a strong ability to resist interference from external inorganic ions and organic matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0032] Figure 1 Characterization diagrams of CoSAs-ZnO of Example 1 and ZnO of Comparative Example 1, wherein a is an X-ray diffraction spectrum, b is a Fourier transform infrared spectrum, and c is a synchrotron radiation absorption spectrum of CoSAs-ZnO.

[0033] Figure 2 This is the spherical aberration electron microscope image of CoSAs-ZnO.

[0034] Figure 3 It is the performance diagram of the degradation of sulfamethoxazole under the conditions of Test Examples 1-5, wherein a is Test Example 1-3 and b is Test Example 4-5.

[0035] Figure 4 It is the performance diagram of the degradation of sulfamethoxazole under the conditions of Test Examples 6-9, wherein a is the SMX removal rate of Test Example 6, b is the degradation curve of SMX in Test Example 8, c is the SMX removal rate of Test Example 7, and d is the degradation curve of SMX in Test Example 9.

[0036] Figure 5 The pH changes when sulfamethoxazole is degraded under the conditions of Test Example 10-11.

[0037] Figure 6 It is the removal rate of sulfamethoxazole by cyclic degradation in Test Example 12-13.

[0038] Figure 7 (a) is the ESR spectrum of sulfate radicals in the CoSAs-ZnO / PMS system, and (b) is the ESR spectrum of singlet oxygen in the CoSAs-ZnO / PAA system. DETAILED DESCRIPTION

[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0040] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0044] Example 1

[0045] The preparation steps of the surface hydroxylated single atom catalyst (CoSAs-ZnO) having a Co-O-Zn structure include:

[0046] S1. Dissolve 2 g of anhydrous zinc acetate and 0.1 g of cobalt acetate tetrahydrate in 48 mL of methanol and continue stirring for 10 min to obtain solution A.

[0047] S2, dissolve 4.44 g of dimethylimidazole in 48 mL of methanol and continue stirring for 10 min to obtain solution B;

[0048] S3, pouring the solution B in step S2 into the solution A in step S1, stirring the reaction for 24 hours to obtain a viscous precursor solution;

[0049] S4, washing the viscous precursor solution by centrifugation with methanol for 3 times, and vacuum drying at 60° C. for 12 h to obtain a precursor material;

[0050] S5. Put the precursor material into a porcelain boat, and then sinter it in a muffle furnace. Raise the temperature to 500°C at a heating rate of 2°C / min and keep it warm for 2 hours. After sintering, a surface hydroxylated single-atom catalyst (CoSAs-ZnO) with a Co-O-Zn structure is obtained.

[0051] Example 2

[0052] The preparation steps of the surface hydroxylated single atom catalyst (CoSAs-ZnO) having a Co-O-Zn structure include:

[0053] S1. Dissolve 1 g of anhydrous zinc acetate and 0.05 g of cobalt acetate tetrahydrate in 48 mL of methanol and continue stirring for 10 min to obtain solution A.

[0054] S2, dissolve 4.44 g of dimethylimidazole in 48 mL of methanol and continue stirring for 10 min to obtain solution B;

[0055] S3, pouring the solution B in step S2 into the solution A in step S1, stirring the reaction for 24 hours to obtain a viscous precursor solution;

[0056] S4, washing the viscous precursor solution by centrifugation with methanol for 3 times, and vacuum drying at 60° C. for 12 h to obtain a precursor material;

[0057] S5. Put the precursor material into a porcelain boat, and then sinter it in a muffle furnace. Raise the temperature to 500°C at a heating rate of 2°C / min and keep it warm for 2 hours. After sintering, a surface hydroxylated single-atom catalyst (CoSAs-ZnO) with a Co-O-Zn structure is obtained.

[0058] Example 3

[0059] The preparation steps of the surface hydroxylated single atom catalyst (CoSAs-ZnO) having a Co-O-Zn structure include:

[0060] S1. Dissolve 1.5 g of anhydrous zinc acetate and 0.075 g of cobalt acetate tetrahydrate in 48 mL of methanol and continue stirring for 10 min to obtain solution A;

[0061] S2, dissolve 4.44 g of dimethylimidazole in 48 mL of methanol and continue stirring for 10 min to obtain solution B;

[0062] S3, pouring the solution B in step S2 into the solution A in step S1, stirring the reaction for 24 hours to obtain a viscous precursor solution;

[0063] S4, washing the viscous precursor solution by centrifugation with methanol for 3 times, and vacuum drying at 60° C. for 12 h to obtain a precursor material;

[0064] S5. Put the precursor material into a porcelain boat, and then sinter it in a muffle furnace. Raise the temperature to 500°C at a heating rate of 2°C / min and keep it warm for 2 hours. After sintering, a surface hydroxylated single-atom catalyst (CoSAs-ZnO) with a Co-O-Zn structure is obtained.

[0065] Comparative Example 1

[0066] The preparation steps of zinc oxide catalyst include:

[0067] S1. Dissolve 2 g of anhydrous zinc acetate in 48 mL of methanol and continue stirring for 10 min to obtain solution A.

[0068] S2, dissolve 4.44 g of dimethylimidazole in 48 mL of methanol and continue stirring for 10 min to obtain solution B;

[0069] S3, pouring the solution B in step S2 into the solution A in step S1, stirring the reaction for 24 hours to obtain a viscous precursor solution;

[0070] S4, washing the viscous precursor solution by centrifugation with methanol for 3 times, and vacuum drying at 60° C. for 12 h to obtain a precursor material;

[0071] S5. Put the precursor material into a porcelain boat, and then sinter it in a muffle furnace. Raise the temperature to 500° C. at a heating rate of 2° C. / min, and keep the temperature for 2 hours. After sintering, a zinc oxide catalyst (ZnO) is obtained.

[0072] Figure 1 The following are characterization diagrams of CoSAs-ZnO of Example 1 and ZnO of Comparative Example 1, wherein a is an X-ray diffraction spectrum, b is a Fourier transform infrared spectrum, and c is a synchrotron radiation absorption spectrum of CoSAs-ZnO. As can be seen from the figure, the introduction of cobalt in a does not destroy the physical structure of zinc oxide, and no other diffraction peaks related to cobalt appear, indicating that a cobalt single-atom catalyst has been successfully synthesized; hydroxyl groups exist on the surface of the CoSAs-ZnO catalyst in b; compared with the Co-Co bond in the Co foil and the Co-O bond in CoO in c, the Co in the CoSAs-ZnO catalyst only presents Co-O and Co-O-Zn bonds, proving that the Co in the catalyst presents a single-atom distribution and has an asymmetric configuration of Co-O-Zn. The above results demonstrate the successful synthesis of a surface hydroxylated single-atom catalyst (CoSAs-ZnO) with a Co-O-Zn structure.

[0073] Figure 2 This is a spherical aberration electron microscope image of CoSAs-ZnO. It can be seen from the figure that there are many isolated bright spots in the image. These bright spots are Co single atoms, proving that Co exists in the form of single atoms without clusters and nanoparticles.

[0074] Effect test

[0075] The catalysts prepared in Examples 1-3 of the present invention have similar effects when used for the degradation of sulfamethoxazole (SMX). Therefore, in the following experiment, the catalyst prepared in Example 1 was used to perform the degradation test of sulfamethoxazole (SMX).

[0076] Test Example 1

[0077] The catalysts prepared in Example 1 and Comparative Example 1 were used to activate peroxymonosulfate (PMS) to degrade sulfamethoxazole (SMX). The specific steps of the method are as follows:

[0078] 5 mg of the catalyst was weighed with an analytical balance and added to 50 mL of a 10 mg / L SMX solution. The mixture was stirred magnetically for 5 min to allow the catalyst and the pollutant to reach an adsorption-desorption equilibrium. Then, 94 uL of a 80 mM peroxymonosulfate solution (PMS) was added and the timing reaction was started.

[0079] 1 mL of sample was taken every 1 min for a total reaction time of 6 min. After sampling, the sample was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. After termination of the reaction, the sample was centrifuged at 14,000 rpm for 20 min. The supernatant was injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.

[0080] Test Example 2

[0081] The catalysts prepared in Example 1 and Comparative Example 1 were used alone to degrade sulfamethoxazole (SMX). The specific steps of the method are as follows:

[0082] Weigh 5 mg of the catalyst using an analytical balance and add it to 50 mL of a 10 mg / L SMX solution. Stir magnetically for 5 minutes to allow the catalyst and pollutants to reach adsorption-desorption equilibrium, then start the timing reaction.

[0083] 1 mL of sample was taken every 1 min for a total reaction time of 6 min. After sampling, the sample was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. After termination of the reaction, the sample was centrifuged at 14,000 rpm for 20 min. The supernatant was injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.

[0084] Test Example 3

[0085] The degradation of sulfamethoxazole (SMX) by single peroxymonosulfate (PMS) is as follows:

[0086] 50 mL of 10 mg / L SMX solution was measured and magnetically stirred for 5 min, then 94 uL of 80 mM permonosulfate solution (PMS) was added and the timing reaction was started;

[0087] 1 mL of sample was taken every 1 min for a total reaction time of 6 min. After sampling, the sample was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. After termination of the reaction, the sample was centrifuged at 14,000 rpm for 20 min. The supernatant was injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.

[0088] Test Example 4

[0089] The catalysts prepared in Example 1 and Comparative Example 1 were used to activate peracetic acid (PAA) to degrade sulfamethoxazole (SMX). The specific steps of the method are as follows:

[0090] Weigh 5 mg of the catalyst using an analytical balance and add it to 50 mL of a 10 mg / L SMX solution. Stir magnetically for 5 minutes to allow the catalyst and pollutants to reach adsorption-desorption equilibrium. Then add 15 uL of an 80 mM peracetic acid solution (PAA) and start the timing reaction.

[0091] 1 mL of sample was taken every 1 min for a total reaction time of 6 min. After sampling, the sample was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. After termination of the reaction, the sample was centrifuged at 14,000 rpm for 20 min. The supernatant was injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.

[0092] Test Example 5

[0093] The degradation of sulfamethoxazole (SMX) by single peracetic acid (PAA) is as follows:

[0094] 50 mL of 10 mg / L SMX solution was measured and magnetically stirred for 5 min, then 15 uL of 80 mM peracetic acid (PAA) was added and the timing reaction was started;

[0095] 1 mL of sample was taken every 1 min for a total reaction time of 6 min. After sampling, the sample was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. After termination of the reaction, the sample was centrifuged at 14,000 rpm for 20 min. The supernatant was injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.

[0096] Figure 3The performance diagram of degradation of sulfamethoxazole under the conditions of test examples 1-5, where a is test example 1-3 and b is test example 4-5. As can be seen from the figure, in a, sulfamethoxazole is almost not removed in the presence of PMS alone, indicating that PMS alone cannot oxidatively degrade sulfamethoxazole; in addition, sulfamethoxazole is almost not removed in the presence of ZnO and CoSAs-ZnO catalysts alone, indicating that their adsorption contribution is negligible; ZnO catalyst activates PMS within 6 minutes to achieve a degradation rate of 7.5% for sulfamethoxazole, while CoSAs-ZnO catalyst activates PMS within 6 minutes to achieve an efficiency of 99.8% in degrading sulfamethoxazole. In b, sulfamethoxazole was almost not removed in the presence of PAA alone, indicating that PAA alone could not oxidatively degrade sulfamethoxazole; the degradation rate of sulfamethoxazole by PAA activated by ZnO catalyst within 6 min could reach 7.3%, while the efficiency of sulfamethoxazole degradation by PAA activated by CoSAs-ZnO catalyst within 6 min could reach 98.3%.

[0097] Test Example 6

[0098] In the presence of different concentrations of inorganic ions, the catalyst (CoSAs-ZnO) prepared in Example 1 was used to activate peroxymonosulfate (PMS) to degrade sulfamethoxazole (SMX). The specific steps of the method are as follows:

[0099] The inorganic ions are chloride ion, nitrate ion and sulfate ion, and the corresponding drugs are sodium chloride, sodium nitrate and sodium sulfate, respectively. The addition concentrations are 1mM, 2mM and 5mM, respectively. Among them, the addition mass corresponding to chloride ion (sodium chloride) is 2.9mg, 5.8mg and 14.6mg, respectively, the addition mass corresponding to nitrate ion (sodium nitrate) is 4.25mg, 8.5mg and 21.2mg, respectively, and the addition mass corresponding to sulfate ion (sodium sulfate) is 7.1mg, 14.2mg and 35.5mg, respectively.

[0100] Weigh the inorganic salt corresponding to the inorganic ion of the corresponding concentration and add it to 50mL of SMX solution with a concentration of 10mg / L, then add 5mg of CoSAs-ZnO catalyst, stir magnetically for 5min to allow the adsorption and desorption equilibrium between the catalyst and the pollutant to be reached, then add 94uL of 80mM peroxymonosulfate solution (PMS) and start the timing reaction;

[0101] 1 mL of sample was taken every 1 min for a total reaction time of 6 min. After sampling, the sample was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. After termination of the reaction, the sample was centrifuged at 14,000 rpm for 20 min. The supernatant was injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.

[0102] Test Example 7

[0103] In the presence of different concentrations of inorganic ions, the catalyst (CoSAs-ZnO) prepared in Example 1 was used to activate peracetic acid (PAA) to degrade sulfamethoxazole (SMX). The specific steps of the method are as follows:

[0104] The inorganic ions are chloride ion, nitrate ion and sulfate ion, and the corresponding drugs are sodium chloride, sodium nitrate and sodium sulfate, respectively. The addition concentrations are 1mM, 2mM and 5mM, respectively. Among them, the addition mass corresponding to chloride ion (sodium chloride) is 2.9mg, 5.8mg and 14.6mg, respectively, the addition mass corresponding to nitrate ion (sodium nitrate) is 4.25mg, 8.5mg and 21.2mg, respectively, and the addition mass corresponding to sulfate ion (sodium sulfate) is 7.1mg, 14.2mg and 35.5mg, respectively.

[0105] Weigh the inorganic salt corresponding to the inorganic ion of the corresponding concentration and add it to 50mL of SMX solution with a concentration of 10mg / L, then add 5mg of CoSAs-ZnO catalyst and stir magnetically for 5min to allow the adsorption and desorption equilibrium between the catalyst and the pollutant to be reached, then add 15uL of 80mM peracetic acid (PAA) and start the timing reaction;

[0106] 1 mL of sample was taken every 1 min for a total reaction time of 6 min. After sampling, the sample was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. After termination of the reaction, the sample was centrifuged at 14,000 rpm for 20 min. The supernatant was injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.

[0107] Test Example 8

[0108] In the presence of different concentrations of organic matter (humic acid), the catalyst (CoSAs-ZnO) prepared in Example 1 was used to activate peroxymonosulfate (PMS) to degrade sulfamethoxazole (SMX). The specific steps of the method are as follows:

[0109] The organic matter was humic acid, and the experimental addition concentrations were 1 mg / L, 2 mg / L, and 5 mg / L;

[0110] Preparation of SMX solution (10 mg / L) containing humic acid (1 mg / L): 49.75 mL of SMX solution (10 mg / L) was measured, and 0.25 mL of 200 mg / L humic acid solution was added thereto, and the total volume of the solution was maintained at 50 mL;

[0111] Preparation of SMX solution (10 mg / L) containing humic acid (2 mg / L): 49.5 mL of SMX solution (10 mg / L) was measured, and 0.5 mL of 200 mg / L humic acid solution was added thereto, and the total volume of the solution was maintained at 50 mL;

[0112] Preparation of SMX solution (10 mg / L) containing humic acid (5 mg / L): 48.75 mL of SMX solution (10 mg / L) was measured, and 1.25 mL of 200 mg / L humic acid solution was added thereto, and the total volume of the solution was maintained at 50 mL;

[0113] Weigh 5 mg of CoSAs-ZnO catalyst and add it to the above-prepared solution. Stir magnetically for 5 min to allow the catalyst and pollutants to reach adsorption-desorption equilibrium. Then add 94 uL of 80 mM peroxymonosulfate solution (PMS) and start the timing reaction.

[0114] 1 mL of sample was taken every 1 min for a total reaction time of 6 min. After sampling, the sample was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. After termination of the reaction, the sample was centrifuged at 14,000 rpm for 20 min. The supernatant was injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.

[0115] Test Example 9

[0116] In the presence of different concentrations of organic matter (humic acid), the catalyst (CoSAs-ZnO) prepared in Example 1 was used to activate peracetic acid (PAA) to degrade sulfamethoxazole (SMX). The specific steps of the method are as follows:

[0117] The organic matter was humic acid, and the experimental addition concentrations were 1 mg / L, 2 mg / L, and 5 mg / L;

[0118] Preparation of SMX solution (10 mg / L) containing humic acid (1 mg / L): 49.75 mL of SMX solution (10 mg / L) was measured, and 0.25 mL of 200 mg / L humic acid solution was added thereto, and the total volume of the solution was maintained at 50 mL;

[0119] Preparation of SMX solution (10 mg / L) containing humic acid (2 mg / L): 49.5 mL of SMX solution (10 mg / L) was measured, and 0.5 mL of 200 mg / L humic acid solution was added thereto, and the total volume of the solution was maintained at 50 mL;

[0120] Preparation of SMX solution (10 mg / L) containing humic acid (5 mg / L): 48.75 mL of SMX solution (10 mg / L) was measured, and 1.25 mL of 200 mg / L humic acid solution was added thereto, and the total volume of the solution was maintained at 50 mL;

[0121] Weigh 5 mg of CoSAs-ZnO catalyst and add it to the above-prepared solution. Stir magnetically for 5 min to allow the catalyst and pollutants to reach adsorption-desorption equilibrium. Then add 15 uL of 80 mM peracetic acid (PAA) and start the timing reaction.

[0122] 1 mL of sample was taken every 1 min for a total reaction time of 6 min. After sampling, the sample was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. After termination of the reaction, the sample was centrifuged at 14,000 rpm for 20 min. The supernatant was injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.

[0123] Figure 4 The performance diagram of the degradation of sulfamethoxazole under the conditions of test examples 6-9, wherein a is the SMX removal rate of test example 6, b is the degradation curve of SMX of test example 8, c is the SMX removal rate of test example 7, and d is the degradation curve of SMX of test example 9. Figure 4 It can be seen that the presence of complex anions and natural organic macromolecules did not interfere with the degradation and removal of sulfamethoxazole by the CoSAs-ZnO / PMS system and the CoSAs-ZnO / PAA system, indicating that the CoSAs-ZnO / PMS system and the CoSAs-ZnO / PAA system are suitable for the purification of complex water bodies.

[0124] Test Example 10

[0125] The method for measuring the change in solution pH during the process of using the catalyst (CoSAs-ZnO) prepared in Example 1 to activate peroxymonosulfate (PMS) to degrade sulfamethoxazole (SMX) is as follows:

[0126] 5 mg of CoSAs-ZnO catalyst was added to the SMX solution with pH values ​​of 3.0, 5.0, 7.0 and 8.0 respectively. The detection probe of the pH meter was always submerged in the solution. The solution was stirred for 5 minutes with a magnetic stirrer and the pH value was read. Then 94 uL of 80 mM permonosulfate solution (PMS) was added and a value was read every 1 minute for a total reaction time of 6 minutes.

[0127] Test Example 11

[0128] The catalyst (CoSAs-ZnO) prepared in Example 1 is used to activate peracetic acid (PAA) to degrade sulfamethoxazole (SMX) in a method for measuring the pH change of the solution, and the steps are as follows:

[0129] 5 mg of CoSAs-ZnO catalyst was added to the SMX solution with pH values ​​of 3.0, 5.0, 7.0 and 8.0 respectively. The detection probe of the pH meter was always submerged in the solution. The solution was stirred for 5 minutes with a magnetic stirrer and the pH value was read. Then 15 uL of 80 mM peracetic acid (PAA) was added and a value was read every 1 minute for a total reaction time of 6 minutes.

[0130] Figure 5 The figure shows the change in pH when sulfamethoxazole is degraded under the conditions of Experimental Example 10-11. It can be seen from the figure that no matter how the initial pH of the sulfamethoxazole solution changes in the range of 3 to 8, the CoSAs-ZnO catalyst can stabilize the pH value of the system solution at around 6, which indicates that CoSAs-ZnO has the function of regulating the pH of the solution and can maintain the neutral microenvironment of the system.

[0131] Test Example 12

[0132] The catalyst prepared in Example 1 is used to activate peroxymonosulfate (PMS) to cyclically degrade sulfamethoxazole (SMX). The specific steps of the method are as follows:

[0133] 10 mg of the catalyst was weighed with an analytical balance and added to 50 mL of a 10 mg / L SMX solution. The mixture was stirred magnetically for 5 min to allow the catalyst and the pollutant to reach an adsorption-desorption equilibrium. Then, 625 uL of a 80 mM peroxymonosulfate solution (PMS) was added and the timing reaction was started.

[0134] After 6 minutes of reaction, take a sample of 1 mL, add it to a test tube with sodium thiosulfate solution, shake it well to terminate the reaction. After 6 minutes of reaction, SMX has been completely degraded. Then add 200 mg / L of SMX solution to the solution after the reaction, keep the SMX concentration at 10 mg / L, and then add 625 uL of 80 mM permonosulfate solution (PMS), and continue to start the timing reaction (6 minutes). After the reaction, take a sample of 1 mL, add it to a test tube with sodium thiosulfate solution, shake it well to terminate the reaction. Repeat the above operation five times, for a total of five cycles;

[0135] Finally, the samples after five cycles were placed in a centrifuge and centrifuged at 14,000 rpm for 20 min. The supernatant was then injected into a high-performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.

[0136] Test Example 13

[0137] The catalyst prepared in Example 1 is used to activate peracetic acid (PAA) to cyclically degrade sulfamethoxazole (SMX). The specific steps of the method are as follows:

[0138] Weigh 20 mg of the catalyst using an analytical balance and add it to 50 mL of a 10 mg / L SMX solution. Stir magnetically for 5 minutes to allow the catalyst and pollutants to reach adsorption-desorption equilibrium. Then add 625 uL of 80 mM peracetic acid (PAA) and start the timing reaction.

[0139] After 6 minutes of reaction, take a sample of 1 mL, add it to a test tube with sodium thiosulfate solution, shake it well to terminate the reaction. After 6 minutes of reaction, SMX has been completely degraded. Then add 200 mg / L of SMX solution to the solution after the reaction, keep the SMX concentration at 10 mg / L, and then add 625 uL of 80 mM peracetic acid (PAA), and continue to start the timing reaction (6 minutes). After the reaction, take a sample of 1 mL, add it to a test tube with sodium thiosulfate solution, shake it well to terminate the reaction. Repeat the above operation five times, for a total of five cycles;

[0140] Finally, the samples after five cycles were placed in a centrifuge and centrifuged at 14,000 rpm for 20 min. The supernatant was then injected into a high-performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.

[0141] Figure 6 is the removal rate of sulfamethoxazole by cyclic degradation in Experimental Examples 12-13. It can be seen from the figure that both systems have good cyclic stability, and can still achieve a degradation efficiency of nearly 97% after five cycles, which indicates that the CoSAs-ZnO catalyst prepared by the present invention has good structural stability.

[0142] Test Example 14

[0143] The steps for detecting sulfate radicals of the catalyst prepared in Example 1 in a peroxymonosulfate (PMS) system are as follows:

[0144] Disperse 2mg CoSAs-ZnO in 5mL DMPO aqueous solution (concentration of 100mM), take the mixed solution and put it into a quartz capillary with an inner diameter of 0.9mm, and seal the bottom with a wax seal. Insert the capillary into the EPR test chamber, test and record the first data; add 50uL persulfate solution (80mM) to the above CoSAs-ZnO dispersion, and collect data after 1min and 3min of reaction respectively; then add 100uL SMX solution to the system, and collect data after 1min of reaction.

[0145] Test Example 15

[0146] The steps for detecting singlet oxygen of the catalyst prepared in Example 1 in a peracetic acid (PAA) system are as follows:

[0147] Disperse 2mg CoSAs-ZnO in 5mL TEMP aqueous solution (concentration of 100mM), take the mixed solution and put it into a quartz capillary with an inner diameter of 0.9mm, and seal the bottom with a wax seal. Insert the capillary into the EPR test chamber, test and record the first data; add 50uL peracetic acid solution (80mM) to the above CoSAs-ZnO dispersion, and collect data after 1min and 3min of reaction respectively; then add 100uL SMX solution to the system, and collect data after 1min of reaction.

[0148] Figure 7 Figure a is the ESR spectrum of sulfate radicals in the CoSAs-ZnO / PMS system, and figure b is the ESR spectrum of singlet oxygen in the CoSAs-ZnO / PAA system. As can be seen from the figure, after the catalyst reacts with the oxidant, sulfate radicals and singlet oxygen show strong spectral signals, and the signal intensity gradually increases with the extension of the reaction time, indicating that the CoSAs-ZnO catalyst can efficiently activate peroxymonosulfate in a short time, and highly selectively generate highly oxidizing sulfate radicals or singlet oxygen, thereby efficiently degrading various organic pollutants.

[0149] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0150] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a surface hydroxylated single-atom catalyst having a Co-O-Zn structure, characterized in that the steps include: Zinc acetate and cobalt acetate are used as metal sources, dimethyl imidazole is used as a ligand, mixed and reacted in a solvent, and the surface hydroxylated single atom catalyst with a Co-O-Zn structure is obtained through centrifugal washing, drying and calcination.

2. The preparation method according to claim 1, characterized in that The mass ratio of the zinc acetate to the cobalt acetate is 1-2:0.05-0.

1.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the zinc acetate to dimethylimidazole is 1-2:4-5.

4. The preparation method according to claim 1, characterized in that: The mixing reaction in the solvent is a mixing reaction in methanol, and the reaction time is 20-24 hours.

5. The preparation method according to claim 1, characterized in that: The solvent used in the centrifugal washing is methanol.

6. The preparation method according to claim 1, characterized in that: The drying temperature is 60-80°C and the drying time is 10-12h.

7. The preparation method according to claim 1, characterized in that: The calcination temperature is 400-500°C, the heating rate is 2-5°C / min, and the insulation time is 1-2h.

8. A surface hydroxylated single atom catalyst having a Co-O-Zn structure, characterized in that: The surface hydroxylated single-atom catalyst having a Co-O-Zn structure is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the surface hydroxylated single-atom catalyst having a Co-O-Zn structure as claimed in claim 8 in the degradation of sulfamethoxazole.

10. A method for degrading sulfamethoxazole, characterized in that the steps include: Adding the surface hydroxylated single-atom catalyst having a Co-O-Zn structure as claimed in claim 8 to a solution of sulfamethoxazole, stirring, and after reaching an adsorption-desorption equilibrium state, adding an oxidant to carry out a degradation reaction of sulfamethoxazole; The oxidizing agent includes persulfate or peracetic acid.

Citation Information

Patent Citations

  • Co3ZnC / Co@NGC magnetic wave-absorbing material as well as preparation method and application of Co3ZnC / Co@NGC magnetic wave-absorbing material

    CN111250131A

  • Method for degrading organic pollutants in water by using nitrogen-doped porous carbon anchored monatomic cobalt catalyst to activate persulfate

    CN112408577A

  • Monatomic Mn catalyst, preparation method thereof and application of monatomic Mn catalyst in degradation of antibiotics in water

    CN114950556A

  • Magnetic monatomic cobalt catalyst and method for catalyzing peracetic acid to degrade antibiotics by using magnetic monatomic cobalt catalyst

    CN117599794A

  • Co-C-N catalyst and preparation method and application thereof

    CN119016085A

Cited By

  • ZnO / Co3O4 composite oxide catalyst as well as preparation method and application thereof

    CN121130901A

  • Zno / co3o4 composite oxide catalyst, preparation method and application thereof

    CN121130901B